Physical and chemical characterization of frozen mango pulps sold in Machado, Minas Gerais state, Brazil - Ádrian Rodrigues Oliveira; Luíz Guilherme Malaquias da Silva; Marcela Costa Rocha; Brígida Monteiro Vilas Boas (Revista Agrogeoambiental)
The use of frozen fruit pulps has gained prominence in food trade, as it provides a convenient alternative with adequate nutritional characteristics. Thus, this study was developed in order to evaluate physical and chemical characteristics of frozen mango pulps sold in Machado, state of Minas Gerais, Brazil, to verify if the product complies with the identity and quality standard established by current Brazilian legislation. Four brands (A, B, C, and D) of frozen mango pulps were selected, with five replicates of each, from the same batch and expiration date. The following analyses were performed: color (L* value, hue angle, and chroma), pH, titratable acidity (g citric acid/100 g), soluble solids (°Brix), total solids (g/100 g), and ascorbic acid (mg/100 g). A higher L* value (lighter color) and chroma were identified for brand A when compared to the others. Meanwhile, the brand B pulp had the highest hue angle (88.98), close to 90°, corresponding to yellow. Results for titratable acidity, soluble solids, total solids, and ascorbic acid comply with those specified by the Brazilian legislation for frozen mango pulps—except for pH, which three of the four brands registered values below the permitted level. It was concluded that only one brand of frozen mango pulp sold in Machado complied with the standards specified by current legislation, while pH values lower than the permitted level were registered in the others.